MANUBRIAL INDEX–A RELIABLE GUIDE IN DETERMINING THE SEX OF THE STERNUM - MAKHIJA, KALPANA; MEHRA, SANDHYA; JAIN, AARUSHI; SHARMA, JAG MOHAN (International Journal of Current Pharmaceutical Research, 2023)
Objective: Sexing an unknown skeleton is a very important and difficult process that anatomists and jurists have to fulfill. Sex can be predicted by the sternum with 90% accuracy. It is crucial to predicting age in the middle age range and sternum is particularly useful for it. In the study conducted for sexing the sternum, different measurements were compared and it was found that manubrium alone is a good tool for gender differentiation of the sternum. Methods: Study was conducted on 100 Sternums of known age and sex which were collected from the postmortem room of the forensic department after taking due consent from the attendants of the deceased. Different measurements of manubrium were taken and contrasted for gender differentiation. ANOVA was used to evaluate the statistical significance. Results: It was found that among morphometric criteria of prosternum manubrial index was found to be accurate and reliable along with clear-cut demarcation in length and width of the manubrium sterni of two sex. Conclusion: It was concluded by this study that the manubrial index is a trustworthy tool for sexing sternum and manubrial width could be fairly reliable criterion for determining sex of the sternum.